The redemption narrative in Jostein Gaarder’s prose - Мацевко-Бекерська, Лідія Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article examines the artistic world in the prose by the contemporary Norwegian writer Jostein Gaarder. Due to certain techniques of narrative strategies the author uniquely and exceptionally elaborately formats both the aesthetic space and its receptive horizon. The article studies the receptive level of overcoming the illusion of simplicity and commonness, and to some extent mundanity of human existence / life, mediocrity of existential problems and possibilities to give short answer to extremely laconic author’s questions which in different ways commence the narrative discourse. The research investigates the aspects of “living” in the work, recession into the plot twists and turns (which are rather reminiscent of the transitions from one unsolvable puzzle to another), emotional and psychological immersion into the world of experience, perfectly differentiated at all narrative levels of novels The Ringmaster’s Daughter and The Castle in the Pyrenees.